Feeding Inhibition by Chitosan on Larvae of Spodoptera litura (Lepidoptera: Noctuidae) - Sulistia Ningsih; Nugroho Susetya Putra; Y. Andi Trisyono (Jurnal Perlindungan Tanaman Indonesia, 2020)
The high usage of synthetic insecticides for controlling Spodoptera litura could be detrimental to the environment, especially on non-target organisms. Therefore, more environmentally friendly pest management techniques should be used, for example, using a natural product such as chitosan. The objective of this study was to understand the effect of feeding inhibition by chitosan on the feeding activity of the third instar larvae of S. litura. The feeding inhibition test was carried out using the choice methods in a factorial completely randomized design (CRD) with seven treatments: i.e. chitosan 5×103, 15×103, 25×103, 35×103, 45×103 ppm and profenofos 0.18×103, 0.34×103 ppm, and one control treatment. The test of the choice methods was carried out by three larval laying positions: (1) between the control and treatment feeds (Position A), (2) above the treated feed (Position B), and (3) above the control feed (Position C), and were replicated three times. The non-choice test was done in a completely randomized design (CRD) with seven treatments plus control and were replicated four times. The results showed that the chitosan in the concentration range of 5×103‒45×103 ppm reduced feeding by S. litura larvae by 2.587 to 34.974% in the choice method, and 11.610 to 50,712% in the non-choice method. This feeding inhibition increased significantly with the increment of chitosan concentration. However, the inhibition effects by chitosan was weaker than the inhibition by profenofos LC50 in both tests at a concentration of 0.34×103 ppm: 44.331% and 62.491% respectively. In conclusion, chitosan with a concentration of 45×103 ppm at all larval laying positions showed the highest value of feeding inhibition activity on the third instar larvae of S. litura compared to other chitosan concentrations in both methods.